FasR Regulates Fatty Acid Biosynthesis and Is Essential for Virulence of Mycobacterium tuberculosis - Mondino, Sonia; Vázquez, Cristina L.; Cabruja, Matías; Sala, Claudia; Cazenave-Gassiot, Amaury; Blanco, Federico C.; Wenk, Markus R.; Bigi, Fabiana; Cole, Stewart T.; Gramajo, Hugo; Gago, Gabriela (Frontiers in Microbiology, 2020)
Mycobacterium tuberculosis, the etiologic agent of human tuberculosis, is the world's leading cause of death from an infectious disease. One of the main features of this pathogen is the complex and dynamic lipid composition of the cell envelope, which adapts to the variable host environment and defines the fate of infection by actively interacting with and modulating immune responses. However, while much has been learned about the enzymes of the numerous lipid pathways, little knowledge is available regarding the proteins and metabolic signals regulating lipid metabolism during M. tuberculosis infection. In this work, we constructed and characterized a FasR-deficient mutant in M. tuberculosis and demonstrated that FasR positively regulates fas and acpS expression. Lipidomic analysis of the wild type and mutant strains revealed complete rearrangement of most lipid components of the cell envelope, with phospholipids, mycolic acids, sulfolipids and phthiocerol dimycocerosates relative abundance severely altered. As a consequence, replication of the mutant strain was impaired in macrophages leading to reduced virulence in a mouse model of infection. Moreover, we show that the fasR mutant resides in acidified cellular compartments, suggesting that the lipid perturbation caused by the mutation prevented M. tuberculosis inhibition of phagolysosome maturation. This study identified FasR as a novel factor involved in regulation of mycobacterial virulence and provides evidence for the essential role that modulation of lipid homeostasis plays in the outcome of M. tuberculosis infection.